First Report of Fusarium annulatum Associated with Young Vine Decline in California - Bustamante, Marcelo I; Elfar, Karina; Smith, Rhonda; Bettiga, Larry; Tian, Tian; Torres-Londoño, Gabriel Andrés; Eskalen, Akif (Plant disease, 2022)
From 2018 to 2021 a decline was detected in young vineyards of both wine and table grape (Vitis vinifera L.) in seven counties across California (Kern, Monterey, Napa, Sonoma, Tulare, Yolo, and Yuba). Affected vines showed poor or no growth throughout the season, dieback, sap exudation and internal cankers around the graft union. Lack of feeder roots was detected, indicating weak root development. In some cases, graft failure was associated with the symptomatology in recently established vineyards (<3 years old). A prevalence from 5 to 50% was estimated in 10 vineyards. Affected vines (n=34) were collected by farm advisors and submitted to the laboratory. Symptomatic vines were surface disinfected with 70% ethanol for 1 minute and air dried under sterile conditions. Vascular discoloration around the graft union was observed and inspected by removing the bark using a sterile knife. Isolations were performed from the margin of lesions by placing five wood sections (1×1 mm) per vine onto potato dextrose agar acidified with 0.5 mL/L of 85% lactic acid (APDA) and incubated for 7 days at 25°C in the dark. Even though other fungi associated with young vine decline were isolated and identified as Phaeoacremonium, Ilyonectria, and Botryosphaeriaceae species, Fusarium colonies (Leslie and Summerell, 2006) were the most prevalent among all the symptomatic vines. Pure cultures were obtained by transferring single hyphal tips onto fresh PDA. After 5 days of incubation, colonies formed white aerial mycelium with orange to purple colors on the bottom. Colonies in Spezieller Nährstoffarmer agar (SNA) produced abundant microconidia that were hyaline and ovoid to elliptical, ranging from 5.4 to 10.6 (7.4) × 1.4 to 3.3 (2.4) µm in size (n=50). Straight and slightly curved macroconidia varied from 15.5 to 42.3 (23.7) × 2.6 to 5.0 (3.6) µm in size (n=50). Upon DNA extraction, the translation elongation factor 1α (tef1) and the RNA polymerase II second largest subunit (rpb2) partial gene regions were amplified and sequenced using the EF1/EF2, 5F2/7cR and 7cF/11aR pair primers, respectively (O'Donnell et al. 1998, O'Donnell et al. 2007, Liu et al. 1999). Consensus sequences were compared to the NCBI database using BLAST, showing over 99% similarity with the ex-type sequence of F. annulatum CBS 258.54 (MT010994 and MT010983). A maximum likelihood multi-locus phylogenetic analysis confirmed that all the Californian isolates cluster with F. annulatum strains. Sequences were deposited in GenBank (nos. OK888534 to OK888537). Two representative isolates (UCD9188 and UCD9416) were used for pathogenicity tests. One-year-old 'Chardonnay' vines were inoculated between the second and third node by removing a 5-mm diameter disk of the bark using a sterile cork borer and placing a 5-mm agar plug with actively growing mycelium. Five replicates per isolate including controls with sterile agar plugs were incubated under greenhouse conditions for 2 months. The experiment was performed twice. Symptoms expressed as vascular linear necrotic lesions that ranged from 25.6 to 62.8 mm and the same pathogen was recovered, thus fulfilling Koch's postulates. Fusarium annulatum Bugnic. is a morphologically and genetically diverse species that has been widely known as F. proliferatum and known to be pathogenic in more than 200 plant hosts (Yilmaz et al. 2021). Fusarium spp. have been previously reported to cause young vine decline in Australia and British Columbia, Canada (Highet and Nair, 1995; Úrbez-Torres et al. 2017). To the best of our knowledge, this is the first report of F. annulatum associated with young vine decline complex in California.